Mimesis and experience: a Platonic perspective on Ricoeur's "Time and narrative" - Grethlein, Jonas (Poetics today, 2021)
Ricoeur's Time and Narrative is duly cited in footnotes but does not seem to have had a strong impact on anglophone narratology. One of the reasons for this is certainly Ricoeur's emphasis on plot, which does not harmonize with the focus on consciousness in cognitive narratology. This article suggests that a reconsideration of the concept of mimesis could help build a bridge between Ricoeur's phenomenological approach and cognitive studies in narrative. More specifically, it argues that Plato's discussion of poetry in the Republic, unanimously criticized by modern scholars, can enrich Ricoeur's concept of mimesis. While Ricoeur follows Aristotle, who ties mimesis to plot, Plato, in Republic 2 and 3, considers mimesis an act of impersonation and thereby paves the way to the level of character, on which cognitive narratologists tend to focus. This article first offers a new reading of the Republic's examination of poetry, trying to show that Plato's account of the effects of poetry on the listeners’ souls resonates with current cognitive approaches. Equipped with this reading, it then turns to Ricoeur again. Ricoeur's description of mimesis III, the reader's adoption of the narrative configuration of time in life, remains vague and abstract. Through its focus on the impact of characters on audiences, Plato's idea of mimesis permits us to integrate a cognitivist perspective into Ricoeur's phenomenological account.
Gesehen am 28.06.2022